DIOGENE 2, a distributed Hospital Information System with an emphasis on its Medical Information Content - Scherrer, Jean-Raoul; Lovis, Christian; Borst, François (Yearbook of Medical Informatics, 1995)
DIOGENE 1 has been a mainframe-based centralised HIS with a star network of communication operating on a daily basis with 120 nursing ward units since 1978. Together the limited and costly growth capabilities of such a system with its extreme difficulty in cooperating jointly with other heterogeneous medical systems, with the need for faster networking expansions, led to the new design of a distributed architecture called DIOGENE 2. In 1989, a migration process between DIOGENE 1 and DIOGENE 2 was initiated and is now on the verge of being achieved. During the time of this new expansion of the HIS, it has been easy to cooperate with the decentralisation process of the new hospital organisation as well facilitating the integration of new functionalities like i.e. new WIS architectture, medical office patient histories, integration based upon PCs with UNIX based client/server platforms. That approach combines the handling of paragraphs structured patient records with the use of medical natural language processing and semi-automatic encoding as well. Amongst these new functionalities the P ACS are associated with image manipulation platforms called OSIRIS for X-Ray images as well as other tools devoted to molecula biology and genetics up to the ExPASy server on Internet using WWW Mosaic which is accessible from all over the world. The distributed architectture appears well suited not only for the integration of these new functionalities but to keep them growing as smoothly as possible.
Keywords: Hospital Information Systems (HIS); distributed architecture computer-based patient record; PACS; image manipulation; WWW /Mosai